Identifying potential parameters associated with response to switching from a PDE5i to riociguat in RESPITE. (15th October 2020) - Benza, Raymond L.; Corris, Paul A.; Klinger, James R.; Langleben, David; Naeije, Robert; Simonneau, Gérald; Ghofrani, Hossein-Ardeschir; Jansa, Pavel; Rosenkranz, Stephan; Scelsi, Laura; Thenappan, Thenappan; Raina, Amresh; et al.
Abstract: Background: RESPITE evaluated patients with pulmonary arterial hypertension and an inadequate response to phosphodiesterase type 5 inhibitors (PDE5i) who switched to riociguat. This post hoc analysis assessed response to this switch in parameters associated with clinical improvement. Methods: RESPITE was a 24-week, uncontrolled pilot study (n = 61). Differences in functional, hemodynamic, and cardiac function parameters, REVEAL risk score (RRS), and biomarkers were compared between responders (free from clinical worsening, World Health Organization functional class I/II, and ≥30 m improvement in 6-min walking distance at Week 24) and non-responders. Results: Of 51 patients (84%) completing RESPITE, 16 (31%) met the responder endpoint. At baseline, there were significant differences between responders and non-responders in N -terminal prohormone of brain natriuretic peptide (NT-proBNP), growth/differentiation factor 15 (GDF-15), and RRS, whereas there were no differences in hemodynamics or cardiac function. At Week 24, responders had significant improvements in pulmonary arterial compliance, pulmonary vascular resistance, and mean pulmonary arterial pressure, while non-responders showed no significant change. Cardiac efficiency and stroke volume index significantly improved irrespective of responder status. Conclusions: NT-proBNP, GDF-15, and RRS were identified as potential predictors of response in patients switching from PDE5i to riociguat. Further prospective controlled studies are needed to confirm the association of these parameters with response. Highlights: In RESPITE, 51 patients switched to riociguat from sildenafil or tadalafil. Exercise capacity, biomarkers & functional class improved from baseline to Week 24. Sixteen patients (31%) met a combined responder endpoint of clinical improvement. At baseline, responders had higher REVEAL risk scores and exercise capacity. Hemodynamic and cardiac function parameters improved in responders at Week 24.